Characteristics of Metachronous Gastric Tumors after Endoscopic Submucosal Dissection for Gastric Intraepithelial Neoplasms. (11th February 2014) - Boda, Tomoyuki; Ito, Masanori; Oka, Shiro; Kitamura, Yoko; Numata, Norifumi; Sanomura, Yoji; Matsuo, Taiji; Tanaka, Shinji; Yoshihara, Masaharu; Arihiro, Koji; Chayama, Kazuaki
Abstract : Background. Recently, endoscopic submucosal dissection (ESD) has become a standard treatment method for early gastric cancer and concurrent stomach preservation. However, metachronous recurrences have become a major problem. We evaluated the incidence and clinicopathologic features of and examined the risk factors for metachronous gastric tumors. Methods. A total of 357 patients who underwent ESD for gastric tumors (245 early gastric cancers and 112 adenomas) and were followed up for more than 12 months without recurrence within the first 12 months were enrolled. We investigated the incidence and clinicopathologic features of metachronous tumors after ESD. We also analyzed the potential risk factors for metachronous tumors using the Kaplan-Meier method and Cox's proportional hazards model. Results. The annual incidence of metachronous tumors after ESD was 2.4%. The median period until discovery after initial ESD was 26.0 months, and the median observation period was 52.6 months. Male patients developed metachronous tumors more frequently (P = 0.04 ), and the hazard ratio of female to male patients was 0.36 (95% confidence interval: 0.11–0.89). Conclusions. Patients with a previous history of gastric tumors have a high risk of subsequent gastric tumor development and male patients should be carefully followed up after ESD for gastric tumor.